Sustainable Livelihoods Approach Pada Saat Gelombang Tinggi Masyarakat Nelayan Di Desa Glondong Gede Kecamatan Tambakboyo Kabupaten Tuban - Royali, Ahmad Sayuti (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The study aims to determine the sustainable livelihood of fishing communities in Glondong Gede Village, Tambakboyo District, Tuban Regency using the concept of Sustainable Livelihood Approch. This study uses a qualitative approach with data collection methods by conducting interviews and documentation. Furthermore, to determine the strength of sustainable livelihoods using Multidemensional Scaling Rapfish calculations. The results of this study show that there are two aspects of assets that are the main strength in the sustainable livelihood of fishermen, namely physical assets with an index of 77.96 and social assets with an index value of 81.84. Keywords: Fishing Communities; Sustainable Livelihood; Multidimensional Scaling Rapfish.